ANNOUNCEMENTS (Journal of Finance, 2023)
AFA Elections: The 2023 AFA elections will again take place online. All voting-eligible AFA members should receive an email in mid-October with a direct link to an individual ballot. If you do not receive this email or if you are unable to vote online please contact [email protected]. Please look at the biographical sketches on the ballot and then vote by the deadline. The AFA 2024 Annual Meeting will be held January 5–7, 2024 (Friday, Saturday, and Sunday) in San Antonio, Texas: ASSA Headquarters will be the Grand Hyatt San Antonio and the AFA hotel will be the Marriott Rivercenter. Registration and Housing information will be available on the AEA website – attendees must go through the official housing company to get the convention rates. NOTE: Conference details are subject to change – please watch the ASSA website for the latest updates at https://www.aeaweb.org/conference/. AFA Financial and Board Meeting Summaries: The AFA Board of Directors has voted to publish a Board Meeting Summary to increase transparency of AFA governance and decisions made by the Board. Recent Board Meeting Summaries as well as AFA Financial Statements are posted on the AFA website (www.afajof.org). We hope that this additional communication is informative and we welcome your feedback. Other Announcements: Please go to our website, www.afajof.org, for announcements regarding AFA news, meetings, onferences, and research support.